WASTE REDUCTION AT PT. X WITH LEAN MANUFACTURING APPROACH - Ramadhan, Angelio Pratama; Ratnasari, Lisa; Sulistyadi, Kohar (Universitas Sahid, 2023)
In 2020 PT. X produces approximately 220 thousand packaging, this causes the paper raw materials used to exceed the maximum limit or exceed the insheet determined by the company. So that there is a loss to the company, both in terms of material and time. There are 3 types of waste or damaged products that are most dominantly found using lean manufacturing methods. The three most dominant wastes are excess insheet, non-standard color and excess glue. The application of lean manufacturing is expected to reduce waste in 2020 and maximize the profits obtained. In implementing lean manufacturing, it is supported by using value stream mapping methods and process activity mapping which is expected to get factors that cause waste. Waste that occurred in 2020 averaged 7.82%, greater than the standard set by the company with an average of 5%.